Aetiology of Total Knee Arthroplasty (TKA) Failure and Assess the Functional Outcome of Patients Who Underwent Revision Total Knee Arthroplasty - Syed Bakht Sardar, Lubna Shah, Kamran Saeed, Fazl Ur Rahman Saeed, Raza Askari, Manqoosh Ur Rehman, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To identify the causes of total knee arthroplasty (TKA) failure and assess the functional results of patients who received revision TKA. Study Design: Descriptive Study Place and Duration: Orthopedic department of Khyber Teaching Hospital Peshawar in the duration from 1st June, 2022 to 30 November, 2022 Methods: The study included all patients who had undergone initial TKA and subsequently underwent revision TKA. Functional outcomes following revision TKA were assessed at six months using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire, and the revision arthroplasty criteria were validated. Statistical significance was determined using a t-test that compared patients' WOMAC scores before and after surgery. Results: A total of 312 revision TKAs were performed on 200 patients in the study, with 89.6% of them transferred to our center. Sixty-nine percent of patients who underwent TKA required a further revision procedure. Over four fifths (73.7%) of all revisions were made after the event. 122 (38.1%) of the cases had been resolved in some fashion. The most common reason for a second surgery after an initial replacement was infection (36.1%), followed by aseptic loosening (21.9%) and periprosthetic fracture (13.7%). The majority of our patients who underwent a second arthroplasty were happy with the functional outcomes. Conclusion: The three most common reasons for a TKA to fail are infection, periprosthetic fracture, and aseptic loosening. Significant improvements in functional outcomes were seen with revision TKA, albeit a sizable proportion of patients still suffered or required additional intervention. Keywords: TKA, Infection, Revision of surgery